2010
DOI: 10.1002/mrm.22457
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte shape reversion from echinocytes to discocytes: Kinetics via fast‐measurement NMR diffusion‐diffraction

Abstract: Pulsed field-gradient spin-echo (PGSE) NMR spectroscopy via q-space plots can characterize erythrocyte shapes and their evolution. The present study employed PGSE NMR to investigate shape reversion from advanced echinocytic to normal discocytic shapes due to depletion and then readdition of Mg 21 . In q-space plots of the data, the diffusion-diffraction minima disappeared for Mg 21 -depleted erythrocytes and reappeared during the shape recovery process, but with lower definition than for control cells. Shape e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…This last conclusion corroborates the work done in Ref. 9, where an increase of cholinecointaining phospholipid concentration of a shape-recovered RBC after a Mg 2þ depletion was observed, compared with the control, suggesting a change in the membrane lipidic distribution.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This last conclusion corroborates the work done in Ref. 9, where an increase of cholinecointaining phospholipid concentration of a shape-recovered RBC after a Mg 2þ depletion was observed, compared with the control, suggesting a change in the membrane lipidic distribution.…”
Section: Discussionsupporting
confidence: 92%
“…These deformations are produced at a constant volume and the erythrocyte can recover its original form through the removal of the drug from the medium. 3,4,8,9 Drugs effects in RBCs have been studied principally through Electron Microscopy. These observations have led to a significant understanding of the morphologies with a very high concordance with theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…At increased ionic strength (or osmolarity) red blood cells can form echinocytes (or burr cells) losing their discoid shape and gaining small protrusions on their surface, associated with separation of the lipid bilayer from the underlying membrane skeleton ( Liu et al., 1989 ), and similar effects are observed in vivo in various situations where the cells are under stress. Previous work using 1 H NMR suggests that echinocyte formation is associated with changes in the distribution of phospholipids between the two leaflets of the cell membrane ( Pages et al., 2010 ). It has recently been shown that reconstituted egg phospholipids show an NOE -1.7ppm peak ( Zhang et al., 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was claimed to require only one transient per free induction decay (FID) to obtain ‘good’ artefact suppression . Pagès et al demonstrated that this experiment could be used to probe reversion of RBC echinocytes to discocytes by monitoring changes in water diffusion every ~5 min . A slightly simplified version of this pulse sequence was also used to measure diffusion in RBC suspensions in order to monitor morphological evolution of discocytes to echinocytes and spherocytes upon metabolic inhibition with NaF; this allowed estimation of the average cell diameter with a time resolution of a few minutes …”
Section: Theory Of Methodsmentioning
confidence: 99%